Cartoons on Tun...and others : a collection - Zunar; Gan, Steven (Kuala Lumpur : Kinibooks, 2006)
Caricatures and cartoons on politics and government in Malaysia
Cover title
In English, with some cartoons in Malay
Keywords: Caricatures and cartoons -- Malaysia; Malaysian wit and humor, Pictorial; Malaysia -- Politics and government -- Caricatures and cartoons